Η ποιότητα ζωής των ασθενών με καρδιακή ανεπάρκεια - Αδάμου, Νίκη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Introduction: Heart failure (HF) is a clinical syndrome in recent years the incidence is increasing more and more. Patients with HF problems such as long-term care and disability which affects the quality of life. Several studies seem to emphasize the effect of HF on quality of life of people. Purpose: The literature review aimed to investigate the quality of life of people with HF. Methods: It is a systematic review study. The literature search was on electronic databases PubMed, Medline and Google Scholar. The literature search was carried out by the end of November 2011 until the end of January 2012. Results: We found a total of 10 studies. According to the results of the quality of life of patients with HF is characterized reduced. Factors that seem to affect negatively the quality of life are gender, age, severity of disease, comorbidity and education level. The dimensions of quality of life of people who were affected by the HF are physical health, emotional health and the bodily pain. Conclusion: The measurement of quality of life contributes to a comprehensive assessment of the health status of individuals by health professionals and nurses in particular. The determination of quality of life and factors affecting it gives nurses the opportunity to design an appropriate individualized management program HF.
Keywords: Heart Failure; Quality of life; Καρδιακή ανεπάρκεια; Ποιότητα ζωής